2021
DOI: 10.1016/j.jiac.2021.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance in hospitalized children with infectious diseases in Japan: Pre- and post-coronavirus disease 2019

Abstract: Introduction The epidemic of coronavirus disease 2019 (COVID-19) rapidly spread worldwide, and the various infection control measures have a significant influence on the spread of many infectious diseases. However, there have been no multicenter studies on how the number of hospitalized children with various infectious diseases changed before and after the outbreak of COVID-19 in Japan. Methods We conducted a multicenter, prospective survey for hospitalized pediatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 29 publications
7
60
0
Order By: Relevance
“…This finding is similar to an earlier study in 2009-2014 in Southern China where influenza, RSV and ADV were found to be the most common respiratory viruses (Zhang et al, 2014;Liao et al, 2015). Most of our samples were collected from outpatients and hence better reflected respiratory virus activity in the community, when compared to studies which focused on hospitalized patients and may be affected by revised admission criteria as part of the pandemic response (Fukuda et al, 2021;Liu et al, 2021). In early 2020 when the most stringent control measures against COVID-19 were implemented, influenza viruses among children and adults were suppressed to a historically low level in Guangzhou as well as in many parts of the world (Olsen et al, 2020;Zipfel et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…This finding is similar to an earlier study in 2009-2014 in Southern China where influenza, RSV and ADV were found to be the most common respiratory viruses (Zhang et al, 2014;Liao et al, 2015). Most of our samples were collected from outpatients and hence better reflected respiratory virus activity in the community, when compared to studies which focused on hospitalized patients and may be affected by revised admission criteria as part of the pandemic response (Fukuda et al, 2021;Liu et al, 2021). In early 2020 when the most stringent control measures against COVID-19 were implemented, influenza viruses among children and adults were suppressed to a historically low level in Guangzhou as well as in many parts of the world (Olsen et al, 2020;Zipfel et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…In most countries with active respiratory virus surveillance, the "traditional" autumn-winter epidemic surge of respiratory syncytial virus (RSV), influenza, and other respiratory viruses was completely blunted [154]. For gastrointestinal viruses, epidemiological surveillance is in generally incomplete; nevertheless, a similar phenomenon was observed, particularly for NoV [155][156][157][158][159][160]. Several hypotheses can be generated to explain this significant decrease, including (i) school closures, leading to massive reductions in gatherings of children and children with adults; (ii) prolonged and intense quarantines; (iii) massive increases in hand hygiene procedures; (iv) global masking; (v) reduction in enteric pathogen testing capacity; and (vi) possible secondary effect of SARS-CoV2 infection (which can replicate on the gastrointestinal epithelium) on the predisposition to other enteric viruses, e.g., altering the gut microbiota composition or inducing an antiviral IFN response [157,160].…”
Section: Lessons From the "Coronavirus Pandemic"mentioning
confidence: 99%
“…The unfolding novel coronavirus disease (COVID-19) pandemic is an unprecedented public health crisis in the modern history of humankind. One collateral consequence of this pandemic is the concomitant rapid decrease in the incidence of viral gastroenteritis in the first year of the pandemic, as observed in many countries, such as China ( 1 ), the United States ( 2 ), England ( 3 ), Germany ( 4 ), Japan ( 5 ), and Australia ( 6 ). The most likely explanations were reduced testing capacity that led to underreporting and wide implementation of nonspecific nonpharmaceutical interventions for COVID-19, such as frequent handwashing and physical distancing, that reduced human-to-human transmission of different viruses.…”
mentioning
confidence: 99%